Financialization and Fictitious Capital: The Rise of Financial Securities as a Form of Private Property - Yair Kaldor (Review of Radical Political Economics, 2022)
In recent decades, financial securities have become a dominant form of private property, accounting for much of the growth of wealth around the world. But what kind of property are financial securities? What are the sources of the income they provide, and what are the social relations that underlie its flow? This article addresses these questions through the Marxist category of fictitious capital. Focusing on corporate stocks and bonds, the article shows that the social relations expressed in these securities are based on the relation of capital and labor and the exploitation of workers in the sphere of production. It concludes that although the rise of financial securities leaves the basic conflict between capital and labor intact, it opens new strategies within this class struggle.
Keywords: B51; E44; P10; 330; Class; Property; Finance; Capital Accumulation